Intergenerational transmission of long-term sick leave - Malin Josephson; Nina Karnehed; Erica Lindahl; Helena Persson (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2013)
The aim of this study is to investigate the importance of intergenerational transmission of sick leave using universal Swedish register data on the rate of sickness benefits. We find that there is a positive correlation between parents' and their children's sick leave. The child-parent correlation is of about the same magnitude irrespective of the gender of the parent and the child, but it is larger the more sick leave the parent had when observed. Furthermore, there is a positive correlation between the sick leave level of the children and that of the parents-in-law, implying that persons tend to live with a partner whose sick leave resembles that of their parents. Finally, a comparison between siblings of different birth order shows that firstborn daughters report fewer spells of sick leave than their younger siblings of the same gender. This gap only emerges in the group of daughters with parents who lack sick leave themselves, suggesting that the birth-order effect is only of importance among women with low levels of sick leave.
Keywords: I14; I15; I10; 330; intergenerational mobility; sickness absence; sickness benefits and disability pension